Analisis Kompetitif Bank Syariah Karang Kobar Melalui Pendekatan Porter’s Five Forces - Fathonah, Aenia Latif; Pratami, Luthfi Ranawati; Depisari, Unik; Shafrani, Yoiz Shofwa (Universitas Maritim AMNI Semarang, 2025)
This study aims to analyze the competitive advantage strategy of Islamic Banks using the Porter's Five Forces approach, which is used to understand the competitive position of Islamic Banks in facing the dynamics of the financial industry that continues to grow. This study includes qualitative research methods with the approach of Field research and Library research, which are supported by interviews or observations as the main data collection techniques. The results of the study indicate that the Threat of New Entrants BSI Karang Kobar is aware of the threat of new entrants and faces internal challenges, especially in the marketing aspect which is still low. Customer strength is shown through the influence of satisfaction with products and employee behavior on loyalty, especially on flagship products such as KPR, gold installments, and micro financing. Supplier strength shows that there is a great opportunity for suppliers to establish partnerships with Islamic financial institutions. The threat of substitute products has not been found directly, but digital transformation to the Byond By BSI platform is a concern. In industrial competition, BSI Karang Kobar admits that it still faces challenges, such as limited economies of scale compared to conventional banks. Thus, the application of sharia principles in the formulation of business strategies allows Islamic banks to build customer loyalty and create sustainable competitive advantages. Porter's Five Forces approach has proven to be relevant and effective in helping Islamic banks formulate adaptive and valuable strategies in facing competition in the modern financial industry.